'Breaking the binary' :exploring the scope of architechture to function as a social catalyst towards social inclusion of the third gender - Abonee, Ishita Alam (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.